Foreign direct investment, home country institutions, and local human development in Brazil - Silva, Eduardo Polloni (Universidade Federal de São Carlos, 2020)
Multinational companies (MNCs) are influenced by their home country institutions. But how does the interaction between home country and host region institutions affect human development in countries with significant regional disparities? To address this question, we collected a unique dataset of FDI from 52 countries in 92 Brazilian municipalities and created a Home Country Institutional Index (HCII). Econometric analyses show that a higher share of foreign companies from countries with high levels of human development is positively associated with local education, health, and income. However, this effect is non-linear and more pronounced in institutionally weak regions.
Investimento direto estrangeiro, instituições de origem e desenvolvimento humano local no Brasil
Keywords: Human development; Foreign direct investment; Home country institutions; Regional institutions; Threshold regression; Desenvolvimento humano; Investimento direto estrangeiro; Instituições de origem; Instituições regionais; Regressão por limiar; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA REGIONAL E URBANA::ECONOMIA REGIONAL; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA DO BEM-ESTAR SOCIAL; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA